Actinomycin D synergistically enhances the cytotoxicity of CDDP on KB cells by activating P53 via decreasing P53–MDM2 complex. Issue 6 (3rd June 2017) - Wang, Lin; Pang, Xiao-Cong; Yu, Zi-Ru; Yang, Sheng-Qian; Liu, Ai-Lin; Wang, Jin-Hua; Du, Guan-Hua
Abstract: The aim of this study is to investigate the synergism of low dose of actinomycin D (LDActD) to the cytotoxicity of cisplatin (CDDP) on KB cells. The role of P53 reactivation by LDActD in the synergism and its mechanism were further studied. Cell viability was determined by MTT assay. Apoptosis was determined by AnnexinV-FITC/PI staining. Mitochondrial membrane potential (MMP) was detected by JC-1 staining. Expression of proteins was detected by Western blotting (WB) and/or immunofluorescence (IF). Molecular docking of actinomycin D (ACTD) to Mouse double minute 2 homolog (MDM2) and Mouse double minute 2 homolog X (MDMX). MDMX was analyzed by Discovery Studio. The content of P53–MDM2 complex was detected by ELISA assay. The cytotoxicity of CDDP was increased by the combination of LDActD in kinds of cancer cells. Molecular docking showed strong interaction between ACTD and MDM2/MDMX. Meanwhile, LDActD significantly decreased P53–MDM2 complex. Significant increase of the apoptotic activity by the combination therapy in KB cells is P53 upregulated modulator of apoptosis (PUMA) dependent. In addition to the decrease in MMP, LDActD increased P53 regulated protein and decreased BCL-XL in KB cells. LDActD efficiently enhanced the cytotoxicity of CDDP in cancer cells and induced P53-PUMA-dependent and mitochondria-mediated apoptosis in KB cells. The reactivation of P53 was probably achieved by disturbing the interaction of P53 and MDM2/MDMX. Abstract :